One- versus two-stage septic hip and knee revision surgery: a comparative cohort outcome study with short- to mid-term follow-up - M. M. J. Jacobs; P. J. C. Heesterbeek; K. Veerman; J. H. M. Goosen (Journal of Bone and Joint Infection)
Introduction: One-stage revisions seem to have similar reinfection rates compared to two-stage revisions for the treatment of periprosthetic joint infections based on retrospective cohort studies with a large variety of indications and treatment protocols. This study aimed to compare outcomes between comparable groups of one-stage and two-stage revision patients.